2018
DOI: 10.1016/j.soncn.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Communicating with Patients and Families Around Difficult Topics in Cancer Care Using the COMFORT Communication Curriculum

Abstract: Quality communication skills are essential to oncology nursing, especially given their vital role in cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 49 publications
0
48
0
9
Order By: Relevance
“…As illustrated by the nurses, male nurses have more difficulties in communicating with pediatric patients. Likewise, Wittenberg et al (7), Norouzinia et al (10), and Banerjee et al (5) reported that the age difference between the nurse and the patient was another communication barrier. In fact, it seems the generation gap to be a barrier to nursepatient communications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As illustrated by the nurses, male nurses have more difficulties in communicating with pediatric patients. Likewise, Wittenberg et al (7), Norouzinia et al (10), and Banerjee et al (5) reported that the age difference between the nurse and the patient was another communication barrier. In fact, it seems the generation gap to be a barrier to nursepatient communications.…”
Section: Discussionmentioning
confidence: 99%
“…It is hard for me to communicate with children... it is hard; I really can't do it…" Participant No. 7 Another participant said:" …Men are more rigid in their relationships because all they have is their pride. A man should be strong and proud..." Participant No.…”
Section: Theme No 3: Communication With Opposite Gender Patients As a Missing Factor In Nursingmentioning
confidence: 99%
See 2 more Smart Citations
“…Meer recent werd het COMFORT-model voorgesteld dat verschillende basisprincipes voor het brengen van slecht nieuws omvat zonder vaste volgorde van deze elementen. Dit model werd uitgewerkt voor communicatie in een palliatieve setting in de humane geneeskunde (Villagran et al, 2010;Wittenberg et al, 2018). De elementen van dit model zijn: een goede dialoog tussen arts en patiënt (Communication), het overlopen van de verschillende diagnostische en therapeutische opties en hun prognose (Orientation and Opportunity), het aandacht geven van de arts aan de patiënt en zijn/haar zorgen (Mindful communication), de aanwezigheid van familie van de patiënt (Family), het identificeren van wat voor de patiënt en zijn/haar familie het belangrijkste is (Opening), rekening houden met het perspectief van de patiënt en zijn/haar familie en indien nodig de boodschap verschillende Eigenaarsperspectief bevragen "Voor we de resultaten bespreken, zou ik er graag zeker van zijn dat we op dezelfde golflengte zitten.…”
Section: Richtlijnen Voor Het Slechtnieuws-gesprekunclassified